(untitled) (International Journal of Engineering Management Science, 2019)
Aluminum metal matrix composites (Al-MMCs) reinforced with nano-sized silicon carbide (SiC) particles offer significant improvements in mechanical properties, making them suitable for aerospace, automotive, and structural applications. This study investigates the effect of nano SiC reinforcement on the mechanical properties of Al7075-based composites synthesized using the stir casting method. The composites were prepared with varying SiC content (2 wt%, 4 wt%, and 6 wt%), and their hardness, tensile strength, and ductility were systematically analyzed. The results demonstrated that increasing SiC content enhances hardness and tensile strength due to effective load transfer and grain refinement. However, higher reinforcement levels led to reduced ductility due to increased brittleness. Hardness tests followed ASTM E92, while tensile testing adhered to ASTM E8 standards. The study highlights the improvement in the hardness of nano SiC reinforced composites along with enhanced strength and ductility.